Studying the Effect of Doping With Aluminum on The Optical Properties Of CdSe Thin Films - A. Shehab, Alia; H. Hussain, Abbas (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
CdSe thin films were deposited on glass sudstrate by thermal evaporation method with thickness of (300Â±25%) nm with deposition rate (2Â±0.1) nm/s and at substrate temperature at (R.T.). XRD analysis reveals that the structure of pure thin films are Hexagonal and polycrystalline with preferential orientation (002). In this research ,we study the effect of doping with (1,2,3)% Aluminum on optical energy gap of (CdSe) thin film . The absorption was studied by using (UV - Visible 1800 spectra photometer ) within the wavelength (300-1100) nm absorption coefficient was calculated as a function of incident photon energy for identify type of electronic transitions it is found that the type of transition is direct , and we calculated the optical energy gap before and after doping we found that the energy gap decreases after doping and absorption coefficient increases.